PENGARUH RELIGIUSITAS, TIPE KEPRIBADIAN, KECERDASAN EMOSI, dan DUKUNGAN SOSIAL TERHADAP STRATEGI COPING (Studi kasus: Mahasiswa D3 Statistika Angkatan 2016 dan 2015) - Muh. Nurul ramadhan; Mukhsar Mukhsar; Makkulau Makkulau (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
This research’s purpose is to know the influence of religiosity, personality, emotional intelligence and social support to cope with stress level on excel students. This research’s population are D3 students of Halu Oleo university, vocational education program in 2015 and 2016. This research is using simple random sampling on 34 students. This research is using 4 variables that are suspected to have influences on how to cope with the stress level on excel students. Those variables are the influence of religiosity, personality, emotional intelligence and social support. This research found that from those 4 variables there’s only one that have influence toward the way to cope with stress level on excel students. That variable is free variable of social support. Then it obtained the multiple linear regression model . From that model it can be seen that if the social support goes up by one point the value on how to cope with the stress level will rise by 0,402 point. Keywords: Religiosity influences, personality, emotional intelligence, social support, coping strategy, simple random sampling, multiple regression model.